Reverse Engineering and Structural Optimization of a Pneumatic Rotary Slip Lifter for Enhanced Safety and Operational Efficiency in Drilling Rigs - A.R.Yosserizal Yosserizal; Rozi Saferi; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2025)
This study presents the reverse engineering and structural optimization of a Pneumatic Rotary Slip Lifter (PSL) to enhance safety and operational efficiency in drilling rig operations. Conventional manual rotary slips expose personnel to ergonomic hazards and reduce handling efficiency during drill pipe manipulation. The existing slip mechanism was digitized through reverse engineering and analyzed using three-dimensional finite element analysis (FEA) to evaluate stress distribution, deformation, and safety factors under operational loading conditions. The optimized design incorporates a pneumatic actuation system operating at 90–120 psi, enabling automated lifting and lowering of the slip assembly. Structural optimization ensured compliance with allowable stress limits while minimizing material usage. Simulation results show a maximum von Mises stress of 103.2 MPa—well below the 250 MPa yield strength—and a minimum safety factor of 2.01, indicating reliable elastic performance. Probabilistic reliability assessment yielded a high reliability index (β ≈ 8.5) and negligible probability of failure, while fatigue analysis confirmed infinite-life behavior under cyclic tripping loads. Operational evaluation demonstrated reduced handling time, elimination of manual lifting, and improved ergonomic safety. The proposed PSL offers a structurally validated, reliable, and economically viable alternative to conventional manual slips, supporting safer and more efficient mechanized drill pipe handling.